2001
DOI: 10.1007/s004410100392
|View full text |Cite
|
Sign up to set email alerts
|

Yolk granules are differentially acidified during embryo development in the stick insect Carausius morosus

Abstract: Newly laid eggs of stick insects comprise a unique fluid ooplasm that is gradually partitioned into a number of yolk granules by invasion of secondary vitellophages. This study aimed at establishing how yolk granules become acidified in the course of embryonic development. Data show that acidified yolk granules are rather scarce and randomly distributed in vitellophages of early embryos, while they tend to increase gradually in number as development proceeds to completion. Yolk granule acidification is progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…If one of these three components is not found in a common vesicle, yolk degradation does not proceed. As highlighted in this paper, the YG population is not homogeneous and it has been extensively shown that YGs can vary in size, density, macromolecule content, and that not all of them undergo acidification during embryogenesis (Postlethwait and Giorgi, 1985;Wallace, 1985;Fagotto, 1995;Chestkov et al, 1998;McNeil et al, 2000;Fausto et al, 2001).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…If one of these three components is not found in a common vesicle, yolk degradation does not proceed. As highlighted in this paper, the YG population is not homogeneous and it has been extensively shown that YGs can vary in size, density, macromolecule content, and that not all of them undergo acidification during embryogenesis (Postlethwait and Giorgi, 1985;Wallace, 1985;Fagotto, 1995;Chestkov et al, 1998;McNeil et al, 2000;Fausto et al, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…In the silkmoth Bombyx mori, the acid enzymes are only present in the small YGs (SYGs), whereas the yolk proteins are localized in the large ones (Yamahama et al, 2003). In the stick insect Carausius morosus, small YGs are frequently more acidic than large YGs and are often seen surrounding the large ones (Fausto et al, 2001). For the hard tick Boophilus microplus, proteolytic activity has also been correlated with differential acidification of YGs and the presence of small vesicles at the periphery of the egg (Abreu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Criel, 1991), formation of yolk platelets (Giorgi et al, 1999;Warner et al, 2002) and yolk degradation (Komazaki and Hiruma, 1999;Perona et al, 1988;Vallejo, 1985, 1989). Indeed, membrane-bound yolk platelets themselves should be considered, as they are acidified to varying degrees for both maintenance and degradation in other species (Abreu et al, 2004;Fagotto, 1995;Fausto et al, 2001) and contain very little P i in A. franciscana (Warner and Huang, 1979). An interesting commonality among all of these compartments is that their final luminal pH is set in part by the V-ATPase proton pump (Futai et al, 1998;Grabe and Oster, 2001;Nishi and Forgac, 2002), and thus this enzyme became the focal point of our research.…”
mentioning
confidence: 99%
“…With the onset of embryonic development, this pro-enzyme is gradually converted to an active proteolytic enzyme by progressive acidification of the yolk granules (Fagotto 1990;Nordin et al 1991;Fagotto & Maxfield 1994;Fausto et al 2001). Following activation of the pro-protease, vitellin polypeptides are degraded by limited proteolysis to generate a number of lower molecular weight Vt cleavage products.…”
Section: Discussionmentioning
confidence: 99%